Barriers to start-up the business among students at tertiary level: a case study in northern states in Malaysia / Azyyati Anuar, Firdaus Abdul Rahman and Ida Normaya Mohd Nasir - Anuar, Azyyati; Abdul Rahman, Firdaus; Mohd Nasir, Ida Normaya (Research Management Institute (RMI), 2012)
Entrepreneurship is not a bizarre subject among Malaysian society where presently most of the Malaysian entrepreneur participating in a various industries and business ventures. Moreover it is one of the government exclamations to achieve developed nation status by 2020 and yet economic growth of 6 per cent a year will be required (PEMANDU). In this line, The Economic Transformation Programme (ETP) has been built on the direction outlined in the Tenth Malaysia Plan to develop a markedly different approach to delivering the government's objectives. In putting Malaysia on the world map, a comprehensive planning need to be taken critically where all parties including public sector, private sectors, students and fresh graduates have to play their important part in ensuring the ETP's will be succeed and also to make Malaysia to become a high-income nation. It was also supported by Minister of Higher Education, Dato' Seri Khalid Nordin where entrepreneurship will be the key enabler for the country to achieve high income nation status by 2020, as the players in the entrepreneurial culture will be the main catalyst to the economic transformation…